The Practice of Authentication: Adapting Pilgrimage from Nenthead into a Graphic Memoir. Issue 1 (7th August 2019) - Dodds, Nick
Abstract : Autobiographical comics have a more conflicted relationship with the truth than explicitly fictional work, due in part to the constraint to fidelity but complicated further by producer-orientated methods of authentication. Every graphic work has a unique expressive style, a transformation through eye and hand which foregrounds the artist's vision, underscoring the process of mediation and subjectivity in interpretation. The structural and visual modality of the comic-book form does not allow for a representational facsimile of the world, involving as it does elements of story compression, visual abstraction and duality in the rendering of text and image. This paper will focus on current doctoral research investigating the graphic memoir, in particular; the authenticating role of the comic-book practitioner in regard to the representation and memorialization of the past and the indexical reference to real-world events and locations. This line of enquiry will be explored via current studio-based practice involving the initial preparation and treatment of a graphic adaptation of Pilgrimage from Nenthead, a working-class memoir written by Chester Armstrong (published by Methuen in 1938 ).